Functional assessment of myocardial ischemia by intracoronary electrocardiogram. (25th November 2020) - Bigler, M.R; Praz, F; Siontis, G.C.M; Stoller, M; Grossenbacher, R; Tschannen, C; Seiler, C
Abstract: Background: In patients with chronic coronary syndrome (CCS), percutaneous coronary intervention (PCI) targets hemodynamically significant stenoses, i.e., those thought to cause ischemia. The hemodynamic severity of a coronary stenosis increases with its tightness and with the myocardial mass of viable myocardium downstream of the stenosis. Besides the structural angiographic approach, assessment of functional relevance by pressure measurements (fractional flow reserve, FFR; instantaneous wave-free ratio, iFR) is recommended. However, visual angiographic assessment continues to dominate the treatment decisions for intermediate coronary lesions. Conversely, intracoronary ECG (icECG) potentially provides an inexpensive, sensitive and direct measure of myocardial ischemia. Purpose: The goal of this study was to test the accuracy of intracoronary ECG during pharmacologic inotropic stress to determine coronary lesion severity in comparison to established physiologic indices (FFR/iFR) as well as with quantitatively determined percent diameter stenosis (%S) using biplane coronary angiography. Method: This was a prospective, open-label study in patients with CCS. The primary study end point was the maximal change in icECG ST-segment shift during pharmacologic inotropic stress induced by dobutamine plus atropine obtained within 1 minute after the point of maximal heart rate (estimated by the formula 220 - age). IcECG was acquired by attaching an alligator clamp to the angioplasty guidewire positioned downstream of a stenosis. For the pressure-derived ratios, i.e. FFR and iFR, the coronary perfusion pressure downstream of a lesion as well as the aortic pressure were continuously recorded. Results: One hundred patients were included in the study. Pearson-Correlation coefficient was significant between icECG and all three comparators (%S p<0.001, iFR p<0.001, FFR p<0.001). Using the FFR threshold of 0.80 defining coronary hemodynamic significance, ROC-analysis of the absolute icECG ST-segment shift showed an area under the curve (AUC) of 0.708±0.053 (p=0.0001, n=100, FFR<0.80 n=41). AUC for iFR was 0.919±0.030 (p<0.0001), for percent diameter stenosis it was 0.867±0.036 (p<0.0001). Conclusions: During pharmacologic inotropic stress, intracoronary ECG ST-segment shift provides specific evidence for regional myocardial ischemia irrespective of the etiology and thus, provides an additional (patho-)physiologic information for decision making in borderline coronary lesions. Funding Acknowledgement: Type of funding source: Foundation. Main funding source(s): Swiss Heart Foundation